Need of Oxygen Administration in Post Anesthesia Care Unit (PACU) with Respect to Type of Anaesthesia and Surgery (Medical Forum Monthly, 2024)
Objective: To determine the frequency of patients needing oxygen administration in PACU with respect to type of anaesthesia and surgery.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Post Anesthesia Care Unit (PACU) of a public sector Tertiary Care Hospital Peshawar during July to September 2019.Materials and Methods: Using consecutive sampling techniques, every patient on arrival at PACU was examined for need of oxygen supplementation and data were noted on structured Performa. A total of 385 sampled patients were included in the study. Data were entered and analyzed by SPSS version 20. Chi Square Test was used to compare need of oxygen with respect to gender, age, site of surgery and types of anesthesia, where p-value <0.05 was considered as significant.Results: A total of 385 surgical patients having mean age of 37.2± 22.2 were observed for oxygen need, out of whom 159(41.3%) were male and 226(58.7%) female. the need of oxygen supplementation was observed only in 62(16.1%) out of whom male accounted for 42(10.9%). Most 28(7.3%). of patients who needed oxygen supplement were belonging to > 60 years while 22(5.7%) were from patient with age of < 5 years old (p <0.001). Similarly majority 46 (11.9%) of them had midline surgery while very few of patient who have surgeries of peripheral site neck region needed oxygen supplementation. Furthermore, 52 (13.5%) of patient who had general anaesthesia with Endotrachial tube and 2 (0.5%) who had GA with Ketamine and Dormicum required oxygen supplementation.Conclusion: An enough amount of oxygen could be saved if oxygen administration to patients is practiced according to the need of patients observed through pulse oximetry. The common factors for hypoxemia among patients in PACU are extreme low and old age, midline surgery and GA with ETT.